Tolvaptan untuk Hiponatremia Euvolemik dan Hipervolemik: Tinjauan Narasi - Terence Judian; Samuel Alexsander (Cermin Dunia Kedokteran, 2024)
Hyponatremia is an electrolyte imbalance disorder commonly found in clinical practice. Hyponatremia is associated with significant mortality and morbidity. Tolvaptan is an orally administered V2 receptor antagonist drug capable of aquaresis without excreting electrolytes, thus increasing plasma sodium concentration. Results from clinical trials showed tolvaptan to be a relatively safe and effective treatment in euvolemia and hypervolemia hyponatremia.